Habitat evaluation of native fishes in the Gila River basin - Hedden, Crosby Kirkpatrick (Kansas State University, 2020)
Habitat loss and alteration is a major cause of declining native fish diversity in streams across the southwestern United States. Much of this habitat alteration is a consequence of human’s actively extracting or diverting water from lotic systems. The Gila River and its tributaries are home to multiple dams, diversions and also supply water to agricultural and industrial municipalities throughout the region, leading to continued decline of native fishes. We conducted a range-wide habitat assessment in an effort to identify critical habitat needs of two endangered minnow species, spikedace (Meda fulgida) and loach minnow (Tiaroga cobitis). This habitat assessment was conducted across multiple spatial scales in an effort to identify at what scale habitat variables most strongly influence the presence of these species. Further, we conducted an enclosure experiment using these two endangered fishes, as well as two other native cyprinids, speckled dace (Rhinichthys osculus) and longfin dace (Agosia chrysogaster), to test mechanisms influencing resource availability and growth rates. Our results point towards water velocity as the driving variable associated with presence and performance of endangered species in this system. We provide guidance on priority habitats and potential repatriation efforts, to ensure that these native species are not lost from this basin.
Keywords: Fish; Habitat